La forme double dans «Le coq et la perle» de Jean de la Fontaine - Calhoun, Doyle (Lingua Frankly, 2014)
This paper examines, using a stylistic approach, one of Jean de La Fontaine's binary-structure fables. The author provides a detailed linguistic and structural analysis of the texts in order to illuminate themes of duality, doubling, transposition, and simultaneous contrast.